INTERCULTURAL COMPETENCE AS ONE BASIC TYPE OF COMMUNICATION COMPETENCE - Feruza Komiljanovna Kurbanova; Nilufar Makhamadjanova (Galaxy International Interdisciplinary Research Journal, 2022)
In this article we aim to discuss approaches on the conceptualization of intercultural competence and it`s study spheres. Some theories related to competence studies we have considered here. The term competence is itself a contested conceptual site. For some time, the term has been too loosely bandied about in scholarly literatures, with surprisingly little attention to its many semantic and conceptual landmines.